Implementing Progressive Management to Improve Business Sustainability and Competitiveness in Gowa Regency - Samsuddin, Samsuddin; Nurnajamuddin, Mahfud; Suryanti (SEAN Institute, 2024)
This research investigates how the village-owned enterprise (BUMDes) management system works in increasing Village Original Income (PADes). The research subjects included parties related to BUMDes Bonto Sunggu Manai and residents of Sunggumanai Village, Gowa, South Sulawesi. This research uses a community service approach with a qualitative descriptive method. The research findings show that although BUMDes management still faces some difficulties, there are improvement plans to be made in the future. Researchers recommend updating the five BUMDes management systems, namely finance, marketing, production, distribution, and human resources. They believe that the role of BUMDes in increasing PADes is not very clear because several management systems are inadequate.